(untitled) (Innovaciones Educativas, 2022)
A reflection is presented in light of the reading of some emblematic works of the Brazilian educator and pedagogue Paulo Freire. Specifically, his description of the pedagogical space is recovered, his relationship with the ideas of inconclusiveness of human nature and his participation in the constitution of the world he inhabits. Using this and other notions, such as naive and epistemic curiosity, this document analyzes what was experienced in the educational field during the time of the pandemic, paying special attention to the way in which the subject was approached from the media, trying to identify In addition, what were the main concerns that emerged from the social group in press releases. In the same way, it reflects on the institutional responses to the problems that intensified with the non-attendance in the classrooms and some academic interpretations in this regard. Throughout the essay, a series of questions are provided to which it is not intended to give answers, but to serve as a provocation for future reflections and dialogues. The essay ends recovering and making more complex the idea of ​​pedagogical space, to talk about a possible pedagogical ecosystem in which the virtuous growth and development of all the people involved in the educational process is ensured.